(untitled) (Asian Journal of Medical Sciences, 2019)
Background: The drug utilization research is a significant constituent of medical audit which helps in monitoring, evaluating and building required modifications in the prescribing practices to attain a rational and cost effective medical care. Aims and Objective: The objective of this study was to evaluate drug utilization design of Nonsteroidal anti-inflammatory drugs (NSAIDs) in a tertiary care teaching hospital, SIMS, Hapur. Material and Methods: This prospective, observational study was conducted in the outpatients of the Pain clinic during six months period to evaluate the prescribing pattern of analgesics in a tertiary care teaching hospital. After getting approval by Institutional Ethical committee, random prescriptions were collected from the OPD and scanned for the record purpose. The demographic data and the prescription were taken from 340 prescriptions. Data was analyzed as per WHO prescribing indicators. Results: A total 340 prescriptions were analyzed. The result revealed that NSAIDs as Diclofenac (75.21%) and Paracetamol (14.88%) were the most commonly prescribed analgesics. Average number of drugs in the present study was found to be 2.29. Percentage of drugs prescribed generic name was (21.02%). Percentage of encounters with an antibiotic was 12.95%, The use of injectable preparation was around 7.20%. Out of all the medicines, 85.90% were found written from Essential Drug List. Conclusion: The prescribing trend of NSAIDs indicate some deviation from the WHO recommendations. This touchstone data will be useful to plan more targeted research and to improve prescribing practices. These types of studies help to design policy for rational use of drugs and perioding training programs of physicians, establishing drug and therapeutic committee, drug information centres and regular educational interventions that can be beneficial for improving prescribing practice with rational drug usage.